APPLICATION OF ANTI OPERATIONS IN PREVENTING NARCOTICS TRAFFICKING - prawira, chandra; Riky Novarizal (Sisi Lain Realita, 2024)
Currently, the illicit trafficking and abuse of narcotics and psychotropic substances targeting the younger generation has reached various corners of the region and the abuse is evenly distributed throughout the social strata of society. As we can see, the number of cases of narcotics abuse in the jurisdiction of the Bengkalis police station is currently increasing greatly and has caused many victims, especially among the younger generation, which is very detrimental to the lives of the community, nation and state. Riau areas that have great potential as areas for drug distribution are Palalawan, Dumai, Pekanbaru and Bengkalis. "Based on the facts that occurred, this research aims to find the application of Antique Operations in Preventing Narcotics Circulation" (Study in the Legal Area of the Bengkalis Police). This type of research is descriptive qualitative using qualitative methods. namely descriptive research. The most practical way to do this is to conduct an in-depth interview. According to Bungin (2007: 108), in-depth interviews are the process of obtaining information for research purposes by means of face-to-face questions and answers between the interviewer and the informant or interviewee, with or without using an interview guide. In this research, the author made key informants and informants the research object. Because by conducting interviews with key informants and informants to get answers from research results related to the Application of Antique Operations in Narcotics Circulation. To overcome the problem of implementing the prevention of narcotics trafficking through secondary and tertiary actions. Actions are taken through counseling, situation control, supervision and so on. This effort is a form of prevention carried out institutionally and in collaboration with community participation. counseling, situation control and supervision are priorities for the police so that these actions can be minimized.